Investigating the Effect of Socio-Demographic Characteristics on the Quality of Life Among Patients with Kidney Stones - Susan Mohammadi-Kebar; Farhad Pourfarzi; Saber Nasiri (Patient Safety and Quality Improvement Journal, 2024)
Introduction: Kidney stones represent a prevalent urological condition, impacting approximately 12% of the global population. While the quality of life has been examined in various urological disorders, research focusing specifically on patients with kidney stones has been limited. This study aims to assess the influence of socio-demographic factors on the quality of life among individuals suffering from kidney stones. Materials and Methods: This cross-sectional analysis involved 142 patients diagnosed with kidney stones. The quality of life was measured using the 36-Item Short Form Health Survey. The data collected were analyzed using SPSS version 25, with results presented as means and standard deviations for quantitative data and frequencies and percentages for qualitative data. The U-Mann-Whitney test was employed to compare quantitative variables between two groups, while the Kruskal-Wallis test was used to compare three or more groups. A sign test evaluated patients' quality of life pre- and post-treatment changes. Results: Patients’ scores varied, with the lowest recorded in the physical role limitations subscale (39.1±37.4) and the highest in the mental health subscale (62.7±15.1). A significant association was found between patients' gender and the subscales of social functioning (P=0.038), bodily pain (P=0.004), and general health (P=0.001). Treatment for kidney stones was shown to impact a patient’s quality of life significantly. Conclusion: Individuals with kidney stones experience a diminished quality of life. Factors such as female gender, age exceeding 50, and obesity were notably linked to a decline in quality of life, whereas no significant correlations were identified with other factors. The treatment of kidney stones significantly contributed to an improvement in the quality of life.